Comparison of fetal weight by ultrasound with actual birth weight - Manandhar Dwa, Yogita; Shrestha, Shreejana; Jaiswal, Pooja; Karki, Prabhat; Maharjan, Dinesh; Ranabhat, Nawaraj; Neupane, Rajendra (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Comparison of fetal weight by ultrasound with actual birth weight is significant for clinical management as it is very closely linked with the survival and well-being of a fetus. Sonographic fetal weight estimation is an essential component of antenatal care. Hence, ultrasonography has become a vital tool in modern obstetrics practice. However, the reliability of the result depends a lot on the quality of the machine and the skill of the sonographer. Actual birth weights are measured with a scale corrected for zero error before use. Methods: This is a retrospective study in which clients under regular follow-up were sent from the Gynaecology and Obstetrics department, undergoing routine antenatal ultrasound to assess fetal well-being. Considering ultrasound at term (37-41 weeks), the data were retrieved, and a comparison was made between fetal weight by ultrasound and actual birth weight. Results: Women, 214 in number, who delivered in Patan Academy of Health Sciences were enrolled in this study. The mean estimated fetal weight was 2995.11(± SD 383.42) grams, and the mean of actual birth weight was 3033.15 (± SD 501.47) grams. The correlation coefficient between fetal weight estimated by USG and actual birth weight was 0.907 (p < 0.001), indicating a strong positive linear correlation. Conclusion: Ultrasonography is an essential tool for estimating fetal weight before delivery in term pregnancies, with no significant difference from actual birth weight.